The phone shop : growth and the entrepreneur. (Part B) - Mitchell, Claire; Beswick, Claire; Zidel, David ([London] : SAGE, 2016)
In August 2009, Eran Brill, director of The Phone Shop (Pty) Ltd, a consumer electronic goods retailer, was about to renegotiate the lease on his Sandton City store. This event marked three years since he had taken over the store, at a time when it was struggling to make sales and to meet its debt obligations. Since then, he had managed to put The Phone Shop onto a much sounder financial footing, and he had opened two more stores. Looking ahead, he wondered whether he could improve on what he had achieved, in the next three years, particularly now that the recession had started to take hold.
Originally Published in: Mitchell, C., Beswick, C., & Zidel, D. (2009). The Phone Shop: Growth and the Entrepreneur (Part B) WBS-2009-17b. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Phone Shop (Firm); Small business -- Finance -- Case studies; Family-owned business enterprises -- Case studies; Strategic planning -- Case studies